Technology Acceptance of ChatGPT Voice Mode in English Speaking Practice: Evidence from International Students in Indonesia - Mufid Lahiria Permata Hati; Juita Triana; Zulia Chasanah (Faculty of Education and Teacher Training of UIN Palopo, 2026)
Non-native English-speaking students in international academic environments often face difficulties in developing speaking skills due to limited opportunities for practice, low confidence, and communication anxiety. Although artificial intelligence (AI)-based tools have been increasingly used to support language learning, limited research has examined international students’ perceptions of ChatGPT voice mode in non-English-speaking educational contexts through the Technology Acceptance Model (TAM). This study explores students’ perceptions of ChatGPT voice mode for English speaking practice, focusing on perceived usefulness, perceived ease of use, behavioral intention, and challenges encountered during its use. A quantitative survey was conducted with ten non-native English-speaking undergraduate students in Indonesia using a 20-item Likert-scale questionnaire, and the data were analyzed descriptively. The results indicate that students generally perceive the feature positively in terms of usefulness and ease of use (M = 3.0–3.4) and demonstrate a willingness to continue using it (M = 3.4). Reported challenges are relatively limited (M = 2.1–2.8), mainly related to speech recognition, accent differences, and limitations in replicating human interaction. Overall, ChatGPT voice mode functions as a supportive tool for independent speaking practice. The findings contribute to research on AI-assisted language learning and provide practical insights for integrating AI-supported speaking tools into language learning environments.